Deprescribing medications for older adults in the primary care context: A mixed studies review - Gillespie, Robyn J. (Health Sci Rep, 2018)
AIMS: This review investigates the factors that influence deprescribing of medications in primary care from the perspective of general practitioners (GPs) and community‐living older adults. METHODS: A mixed studies review structure was adopted searching Scopus, CINAHL, PsychINFO, ProQuest, and PubMed from January 2000 to December 2017. A manual search of reference lists was also conducted. Studies were included if they were original research available in English and explored general deprescribing rather than deprescribing of a specific class of medications. The Mixed Methods Assessment Tool was used to assess the quality of studies, and content analysis generated common categories across studies. RESULTS: Thirty‐eight articles were included, and 7 key categories were identified. The review found that the factors that influence deprescribing are similar across and within health systems and mostly act as barriers. These factors remained unchanged across the review period. The structural organisation of health systems remains poorly suited to facilitate deprescribing. Individual knowledge gaps of both GPs and older adults influence practices and attitudes towards deprescribing, and significant communication gaps occur between GPs and specialists and between GPs and older adults. As a result, deprescribing decision making is characterised by uncertainty, and deprescribing is often considered only when medication problems have already arisen. Trust plays a complex role, acting as both a barrier and facilitator of deprescribing. CONCLUSIONS: Deprescribing is influenced by many factors. Despite recent interest, little change has occurred. Multilevel strategies aimed at reforming aspects of the health system and managing uncertainty at the practice and individual level, notably reducing knowledge limitations and closing communications gaps, may achieve change.